Simulasi Numerik dengan Pendekatan 3D-URANS Aliran yang Melintasi Susunan Empat Silinder Sirkular Dekat Dinding pada “Small-Gap” - A. Grummy Wailanduw; Triyogi Yuwono; Wawan Aries Widodo (Jurnal Teknik Mesin (Sinta 3), 2014)
A flow cross four circular cylinders arrangement in center-line had been many investigated by an experimentally, a simulation, as well as a visualization. The flow phenomena around the cylinders were different when its arrangement were located near a wall, especially at small gap. A boundary layer of the wall would effected a flow characteristics around the cylinders. This research was done by numerical method with FLUENT 6.3.26 software at L/D = 4.0 and G/D rasio 0.1 and 0.2 and Reynolds number 53000 based on the diameter of a single cylinder. An evolution of pressure distributions in circular cylinders, especially at the lower cylinders, are effected of a plane wall which located near them.